Implementation of Single Minute Exchange of Die Method to Reduce Setup Time of Terminal Lead Welding Machine - Nyana Segaran, Laavankumar (Research Progress in Mechanical and Manufacturing Engineering, 2023)
This study is focusing on Single Minutes Exchange Die (SMED) method and other lean tools or system that support or make improvement to the SMED method on the terminal lead welding machine, also known as auto activation cum impulse and medium frequency welding machine at TDK Electronics (Malaysia) Sdn. Bhd. Single Minute Exchange of Die (SMED) is the main lean tool used in this study. Meanwhile, root cause analysis and value stream mapping are used as supporting lean tools in this study. This study focuses to reduce changeover or setup time on the terminal lead welding machine by implementing Single Minute Exchange of Dies (SMED). This study also analyses the changeover process or setup operation and suggests an efficient way to decrease production downtime and, therefore, the production cost of the industry. The SMED methodology began with the data collection of current practices through interview, observation, document review and data analysis. Then, time, value stream mapping (VPM) and root cause analysis (RCA) was conducted to identify current changeover or setup time for each internal and external activity. By externalizing and parallelizing some internal activities, the existing changeover time managed to be reduced by 48.42% from a current 2.3 hours of changeover time by integrating SMED techniques. This leads to the reduction and elimination of wastes from the setup or changeover process of the terminal lead welding machine.